Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12881-017-0367-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary manifestations in Niemann-Pick type C disease with mutations in NPC2 gene: case report and review of literature

Abstract: BackgroundNiemann-Pick disease type C (NPC) is an inherited metabolic disorder; due to defect in cellular cholesterol trafficking. It is clinically a heterogeneous disease with variable age of onset with multiple organ systems being involved. NPC1 gene is involved in 95% cases where as remaining ~5% cases are linked with NPC2 gene.Case presentationCase-1, a 14-months-old female presented with recurrent respiratory distress, failure to thrive and hepatosplenomegaly. Lung biopsy was suggestive of alveolar protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 22 publications
(22 reference statements)
2
11
0
Order By: Relevance
“…Similarly, Guillemot et al reported a high rate of ILD in Niemann‐Pick disease. Few case reports describe PAP in Niemann‐Pick disease . As compatible with the literature, our patients showed typical respiratory manifestations such as chronic airway aspirations, recurrent pneumonia, ILD, and PAP.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Similarly, Guillemot et al reported a high rate of ILD in Niemann‐Pick disease. Few case reports describe PAP in Niemann‐Pick disease . As compatible with the literature, our patients showed typical respiratory manifestations such as chronic airway aspirations, recurrent pneumonia, ILD, and PAP.…”
Section: Discussionsupporting
confidence: 88%
“…ILD may be observed in lysosomal storage disorders (LSD) and lysinuric protein intolerance . Immune defects, such as neutropenia or lymphocyte function impairment, may occur in hereditary orotic aciduria and glycogenosis type 1 and 2 and increase susceptibility to lower respiratory tract infections (LTRI) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipoproteinosis causes severe lung pathology in several other LSDs, such as Gaucher disease and Niemann-Pick disease types B, C1, and C2 (19,46,(51)(52)(53). Corresponding mouse models have been instrumental in characterizing disease progression (10,12,26).…”
Section: Introductionmentioning
confidence: 99%
“…Type a is dueto mutations in SPMD1 (11p15.4)and type b is due to mutations in SMPD2 (6q21). Type cis due to mutations in one of two genes, NPC1 (18q11.2, 95%) or NPC2 (14q24.3, 5%) [ 48 , 49 ]. There are varying degrees of hepatosplenomegaly, and neurological and pulmonary disease, this last predominantly in NPC2 mutations.…”
Section: Aetiologymentioning
confidence: 99%